133k views
0 votes
21+ 6m=3(m-1) not sure what to do here

User Fspirit
by
4.9k points

2 Answers

6 votes

Answer:

m = - 8

Explanation:

Given

21 + 6m = 3(m - 1) ← distribute

21 + 6m = 3m - 3 ( subtract 3m from both sides )

21 + 3m = - 3 ( subtract 21 from both sides )

3m = - 24 ( divide both sides by 3 )

m = - 8

User Sardar Khan
by
4.9k points
6 votes

Answer:

M=-8

Explanation:

21+6m=3(m−1)

Step 1: Simplify both sides of the equation.

21+6m=3(m−1)

21+6m=(3)(m)+(3)(−1)(Distribute)

21+6m=3m+−3

6m+21=3m−3

Step 2: Subtract 3m from both sides.

6m+21−3m=3m−3−3m

3m+21=−3

Step 3: Subtract 21 from both sides.

3m+21−21=−3−21

3m=−24

Step 4: Divide both sides by 3.

3m/3=-24/3

M=-8

User Harsha Pulikollu
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.